The Importance of Updating the 2013 Curriculum with the Independent Curriculum - Sholahuddin Qoffal; Saiful Arif (Institut Nurul Islam Mojokerto, 2025)
This research aims to examine the urgency of updating the 2013 Curriculum with the Merdeka Curriculum as a response to the need for a more adaptive, contextual, and future-oriented education. The method used is a qualitative approach with a library research type, where data is collected through the analysis of relevant documents and literature, and then analyzed using content analysis techniques. The research results indicate that the 2013 Curriculum has several weaknesses, including its overly centralized nature, limited teacher flexibility, and unbalanced material load. As a solution, the Merdeka Curriculum presents three main pillars: project-based learning, focus on essential materials, and a flexible curriculum structure. This curriculum provides space for teachers and students to create more meaningful, personalized, and contextual learning experiences. From this research, it shows that the Merdeka Curriculum is capable of addressing the challenges of 21st-century education, strengthening students' character and skills, and realizing a national education system that is more relevant, inclusive, and transformative.